CCBE1 is required for coronary vessel development and proper coronary artery stem formation in the mouse heart. Issue 10 (21st October 2018) - Bonet, Fernando; Pereira, Paulo N. G.; Bover, Oriol; Marques, Sara; Inácio, José M.; Belo, José A.
Abstract : Background : Proper coronary vasculature development is essential for late‐embryonic and adult heart function. The developmental regulation of coronary embryogenesis is complex and includes the coordinated activity of multiple signaling pathways. CCBE1 plays an important role during lymphangiogenesis, enhancing VEGF‐C signaling, which is also required for coronary vasculature formation. However, whether CCBE1 plays a similar role during coronary vasculature development is still unknown. Here, we investigate the coronary vasculature development in Ccbe1 mutant embryos.Results : We show that Ccbe1 is expressed in the epicardium, like Vegf‐c, and also in the sinus venosus (SV) at the stages of its contribution to coronary vasculature formation. We also report that absence of CCBE1 in cardiac tissue inhibited coronary growth that sprouts from the SV endocardium at the dorsal cardiac wall. This disruption of coronary formation correlates with abnormal processing of VEGF‐C propeptides, suggesting VEGF‐C–dependent signaling alteration. Moreover, Ccbe1 loss‐of‐function leads to the development of defective dorsal and ventral intramyocardial vessels. We also demonstrate that Ccbe1 mutants display delayed and mispatterned coronary artery (CA) stem formation.Conclusions : CCBE1 is essential for coronary vessel formation, independent of their embryonic origin, and is also necessary for peritruncal vessel growth and proper CA stem patterning. Developmental Dynamics 247:1135‐1145, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Ccbe1 is expressed in the epicardium and sinus venosus (SV) myocardium during coronary vasculature development. CCBE1 is required for SV endocardium‐derived coronary vessel development enhancing VEGF‐C processing. CCBE1 is required for the development of the coronary vessels forming at the ventral cardiac side of the heart. CCBE1 is necessary for peritruncal vessel growth and proper coronary artery (CA) stem formation.